Pengembangan Media Pembelajaran Matematika dengan Menggunakan Pop-up Book Jaring-jaring Bangun Ruang - Repa, Putri Akika Jeni; Kamalia, Ghina; Pujianti, Desi; Anggraini, Hidaya; Susanti, Elsa; Meryansumayeka, Meryansumayeka; Zulkardi, Zulkardi (Jurnal Tadris Matematika, 2025)
Geometry materials require visual ability to understand abstract objects, while students in elementary school are still in the concrete operational stage, so they need to understand concepts on real objects. The abstractness of geometry at the elementary school level can be overcome by using pop-up book media. The main objective of this research is to develop mathematics learning media by using pop-up book nets of building spaces. The ADDIE development model was used in this study. Based on the validity test conducted by material experts and media experts, this media falls into the valid category. To see the effectiveness of the props obtained from the results of observations and interviews. Meanwhile, the practicality aspect is seen by evaluating the practicality by teachers and students. According to this assessment, the teacher assigned a score of 54 to the practicality value, while students averaged 60. Both scores obtained are in the practical category. Therefore, the learning media learning pop-up book nets of spaces developed is valid, effective, and practical. Teachers can use this teaching aid as an alternative to encourage engaging learning and improve student understanding, especially in elementary school geometry.